2021
DOI: 10.3897/mycokeys.81.68485
|View full text |Cite
|
Sign up to set email alerts
|

Two new toxic yellow Inocybe species from China: morphological characteristics, phylogenetic analyses and toxin detection

Abstract: Some species of Inocybes. str. caused neurotoxic poisoning after consumption around the world. However, there are a large number of species in this genus that have not been studied for their toxicity or toxin content. In this study, we report two new toxic yellow Inocybes. str. species from China based on morphological characteristics, phylogenetic analyses and toxin detection. Among the two species, Inocybe squarrosolutea is reported as a newly recorded species of China. We also describe a new species, I. squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Brown et al ( 1962 ) found that the contents of muscarine differ in different collections of certain species. Li et al ( 2021b ) detected two toxic Inocybe from China, discovering that the muscarine contents in Inocybe squarrosolutea (Corner & E. Horak) Garrido and Inocybe squarrosofulva (S.N. Li, Y.G.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brown et al ( 1962 ) found that the contents of muscarine differ in different collections of certain species. Li et al ( 2021b ) detected two toxic Inocybe from China, discovering that the muscarine contents in Inocybe squarrosolutea (Corner & E. Horak) Garrido and Inocybe squarrosofulva (S.N. Li, Y.G.…”
Section: Discussionmentioning
confidence: 99%
“…Among these diverse groups of poisonous mushrooms, Inocybaceae is supposed to contain a large number of muscarine-containing taxa. The species diversity of Inocybaceae was documented by a series of studies in China (Fan and Bau, 2010, 2014a,b, 2016Bau and Fan, 2018;Yu et al, 2020;Deng et al, 2021a,b;Li et al, 2021b). Inosperma genus only includes a few toxic species, but a high level of muscarine was frequently detected (Kosentka et al, 2013;Sailatha et al, 2014;Latha et al, 2020;Deng et al, 2021a;Patocka et al, 2021) and was reported constantly in mushroom poisoning incidents from tropical Asia (Chandrasekharan et al, 2020;Parnmen et al, 2021;Li et al, 2022).…”
Section: Introductionmentioning
confidence: 97%
“…Xu et al (2020b) reported that the muscarine content of I. serotina Peck in a poisoning incident was 324.0 ± 62.4 mg/kg wet weight. Li et al (2021b) .23, 11.87 ± 3.02 and [2.08 ± 0.05 (pileus) and 6.53 ± 1.88 (stipes)] g/kg dry weight, respectively. In this study, results showed that P. arenarium is a muscarine-positive species with middle-and upper-level muscarine content and also led to three poisoning incidents with a total of seven patients in northwest China during the past 2 years (Li et al 2021a(Li et al , 2022.…”
Section: Discussionmentioning
confidence: 99%
“… serotina Peck in a poisoning incident was 324.0 ± 62.4 mg/kg wet weight. Li et al (2021b) reported that the muscarine content in I. squarrosolutea (Corner & E. Horak) Garrido and I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation